2002
DOI: 10.1007/s00240-001-0232-3
|View full text |Cite
|
Sign up to set email alerts
|

Histogenesis of nonurothelial carcinomas of the urinary bladder from pre-existent transitional cell carcinomas. A histopathological and immunohistochemical study

Abstract: The histogenesis of nonurothelial carcinomas of the urinary bladder is difficult to understand, since the bladder is normally lined exclusively by transitional cell epithelium. To gain more insights into the pathogenesis of nonurothelial carcinomas, the morphology and immunohistochemistry of transitional cell carcinomas (TCC), mixed transitional cell and nonurothelial carcinomas, and pure nonurothelial carcinomas were comparatively studied. Of papillary and of nonpapillary (solid) TCC (overall incidence 6.8%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…[5] Kunze and Francksen reported that either adenocarcinoma or SCC may arise metaplastically from a pre-existing TCC. [6]…”
Section: Discussionmentioning
confidence: 99%
“…[5] Kunze and Francksen reported that either adenocarcinoma or SCC may arise metaplastically from a pre-existing TCC. [6]…”
Section: Discussionmentioning
confidence: 99%
“…Microscopically, signet ring cells are described as crescent cells, the nuclei of which are compressed to the side of the cell edge by a large number of cytoplasmic mucins. In some tumors, they appear as single clear vacuoles, while in others, they appear as foam like multivesicular cytoplasmic material [3][4][5]. The cumulative distribution of mucin in cytoplasm and nucleus is uneven [6].…”
Section: Introductionmentioning
confidence: 99%